2012
DOI: 10.1097/prs.0b013e3182589b0e
|View full text |Cite
|
Sign up to set email alerts
|

The Distally Based Adipofascial Sural Artery Flap

Abstract: Therapeutic, III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 19 publications
(23 reference statements)
0
17
0
Order By: Relevance
“…Many different modifications of the sural flaps have been made based on its vascular pedicle and flap components [31,32] . …”
Section: Flap Variationsmentioning
confidence: 99%
“…Many different modifications of the sural flaps have been made based on its vascular pedicle and flap components [31,32] . …”
Section: Flap Variationsmentioning
confidence: 99%
“…Although the supercharging technique changes the operation into a more complex microsurgical demanding procedure, the adipofascial technique requires no further skills and is less time-demanding than the classic RSAF. 5 All other modifications showed less improvement compared to the total rates. The venous supercharged flap design was the only modification that reached a statistically relevant difference to the unmodified RSAF in complication rate.…”
Section: Discussionmentioning
confidence: 92%
“… 1 , 2 , 3 , 4 In comparison to more demanding microsurgical free flaps, a common practice used for similar indications, the RSAF bears several advantages, including low donor site morbidity and a shorter operative duration. 5 Furthermore, this technique can be sufficiently adapted and performed by less experienced microsurgeons. Multiple studies reported excellent outcomes for the RSAF; however, discussion includes an uncertainty with the safety of the procedure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the flap is simple to harvest, and can be performed by a single surgeon in under 2 hours. A comparative study supports these advantages and illustrates the adipofascial flap to be as safe as the fasciocutaneous flap [13]. …”
Section: Discussionmentioning
confidence: 98%